ISLAMIC EDUCATION AS A PILLAR OF REHABILITATION: A STUDY OF CHILD INMATE DEVELOPMENT AT LPKA CLASS II MAMUJU - Asnuddin Asnuddin; Muzakkir; M. Rusdi T (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This research is motivated by the importance of Islamic education in fostering child inmates at the Mamuju Class II Special Children's Development Institution (LPKA). Sentenced children still have the right to education, including spiritual and moral guidance that can shape their character for the better. In this context, Islamic education plays a strategic approach in fostering the fostered children's beliefs, worship, and morals. This study aims to describe the form of coaching of faith, worship, and morals in LPKA Class II Mamuju and identify the inhibiting and supporting factors that affect the sustainability of coaching. The method used is a descriptive qualitative approach with field research. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Huberman models. The study results show that coaching is carried out through activities such as learning the pillars of faith, congregational prayers, dhikr, religious lectures, BTQ, tahfidzul Qur'an, habituating manners, and responsibility. The main obstacles faced include limited human resources, facilities, budget, and the psychological condition of children. However, collaboration with external institutions and children's motivation are significant supporting factors. In conclusion, coaching at LPKA Mamuju makes a real contribution to shaping the character of child inmates through Islamic education. This research makes a theoretical and practical contribution to developing a more humanist and integrated coaching model in the future.